Cover Image, Volume 65, Issue 7. Issue 7 (1st July 2020) - Unknown
Abstract : Cover : The Fertilizer Recommendation Support Tool (FRST) is a database and online tool in development to bring together soil fertility information on a national scale. A core team conducted the first nationwide soil fertility and philosophy survey since 1998 to develop minimum requirements for data inclusion in the database. The tool will not only help all those involved in making soil fertility recommendations but will conserve historical soil test data. See story on p. 3. Cover photo courtesy of the United Soybean Board.